Virtual bronchoscopy-guided treatment planning to map and mitigate radiation-induced airway injury in lung SAbR - Kazemzadeh, Narges (Int J Radiat Oncol Biol Phys, 2018)
PURPOSE: Radiation injury to the bronchial tree is an important yet poorly understood potential side effect in lung stereotactic ablative radiotherapy (SAbR). We investigate the integration of virtual bronchoscopy in radiotherapy planning to quantify dose to individual airways. We develop a risk model of airway collapse and develop treatment plans that reduce the risk of radiation-induced airway injury. METHODS AND MATERIALS: Pre- and post-SAbR diagnostic-quality CT scans were retrospectively collected from 26 lung cancer patients. From each scan, the bronchial tree was segmented using a virtual bronchoscopy system and deformably registered to the planning CT. Univariate and stepwise multivariate Cox regression were performed, examining factors such as age, co-morbidities, smoking pack years, airway diameter and maximum point dose (D(max)). Logistic regression was utilized to formulate a risk function of segmental collapse based on D(max) and diameter. The risk function was incorporated into the objective function along with clinical dose volume constraints for planning target volume (PTV) and organs at risk (OARs). RESULTS: Univariate analysis showed that segmental diameter (p = 0.014) and D(max) (p=0.007) were significantly correlated with airway segment collapse. Multivariate stepwise Cox regression showed that diameter (p = 0.015), D(max) (p < 0.0001) and pack years of smoking (p = 0.02) were significant independent factors associated with collapse. Risk-management-based plans enabled significant dose reduction to individual airway segments while fulfilling clinical dosimetric objectives. CONCLUSION: To our knowledge, this is the first systematic investigation of functional avoidance in lung SAbR based on mapping and minimizing dose to individual bronchial segments. Our early results show that it is possible to substantially lower airway dose. Such dose reduction may potentially reduce the risk of radiation-induced airway injury, while satisfying clinically prescribed dosimetric objectives.